Polar magneto-optical Kerr effect spectroscopy with a microscope arrangement for studies on 2D materials - Das, Dibyasankar; Ghosh, Sandip (Review of scientific instruments, 2024)
We describe a setup for magneto-optical Kerr effect (MOKE) spectroscopy suitable for Kerr rotation (ϕ) and ellipticity (η) measurement on microscopic samples, such as flakes of two-dimensional materials. A spatial resolution of ∼25 μm, limited by the demagnified monochromator exit slit image, was achieved. The use of mirrors allows for measurement in polar MOKE geometry with a conventional electro-magnet, without requiring holes in the magnet pole pieces. The microscope-like optics also has a 90° twisted periscope arrangement of two mirrors that helps transport light without change in its circular polarization state. A Jones matrix analysis of the setup brings out the influence of the beam-splitter on the measured signals. Its correction requires the ellipsometry parameters of the beam-splitter in transmission mode, which were measured separately. The working of the setup is tested by measuring the ϕ and η spectra of 2H-WS2 flakes at low temperature, verifying them using Kramers–Kronig analysis and extracting the Landé g-factor of the ground state exciton from them.